This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: step process. ±ind the inverse of f ( x ) = 3 √ x + 2. Step 1: y = 3 √ x + 2 • Write y = f ( x ). Step 2: y 3 = ( 3 √ x + 2) 3 • Solve for x . y 3 = x + 2 y 32 = x Step 3: x 32 = f1 ( x ) • Replace x for y and f1 ( x ) for x . 3. Determine if the function is 11 (Hint: start by graphing the function). If it is Fnd the inverse ( f1 ( x )). a) f ( x ) = 4 x + 3 b) g ( x ) = ( x + 1) 2 c) h ( x ) = ( x + 1) 3...
View
Full
Document
This note was uploaded on 04/14/2008 for the course MATH 138 taught by Professor Hubbard during the Spring '08 term at Stephen F Austin State University.
 Spring '08
 Hubbard
 Inverse Functions

Click to edit the document details